Pemberdayaan Orang Tua dalam Pemantauan Status Gizi dan Imunisasi pada Balita selama Pandemi Covid-19 - Angesti Nugraheni; Atriany Nilam Sari; Sri Mulyani; Vitri Widaningsih; Udi Heru Nefihancoro (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
The Covid-19 pandemic has directly impacted the continuity of children's health services. As many as 10.31% of children experienced delays in immunization, and 17% of toddlers had malnutrition status. The purpose of this service is to provide education for mothers who have toddlers to continue to monitor the nutritional status and immunization of children during a pandemic. The target of this activity is mothers who have toddlers and include members at the Sekolah Komplementer Cinta Ibu as many as 31 mothers. The provision of education is given through a whatsapp group, starting with extracting information about the nutritional status and immunization of children after providing material according to related problems, then giving a questionnaire to find out the level of maternal knowledge. The results showed that 32.26% of toddlers had incomplete basic immunization status, besides that there were still 6.45% with malnutrition status and 9.68% more nutrition, but after providing education, the mother's knowledge level was in the good category. Parents are empowered and aware of the health needs of children, so a quality generation will be created. ABSTRAK Pandemi Covid-19 secara langsung berdampak pada kelangsungan pelayanan kesehatan anak. Sebesar 10,31 % anak mengalami penundaan imunisasi, dan 17% balita berstatus gizi kurang. Tujuan pengabdian ini memberikan edukasi bagi ibu yang memiliki balita untuk tetap melakukan pemantauan status gizi dan imunisasi anak di masa pandemi. Sasaran kegiatan ini adalah ibu yang memiliki balita dan termasuk anggota di Sekolah Komplementer Cinta Ibu sebanyak 31 ibu. Pemberian edukasi diberikan melalui grup whatsapp, diawali dengan penggalian informasi mengenai status gizi dan imunisasi anak setelahnya memberikan materi sesuai dengan masalah terkait, kemudian pemberian kuisioner untuk mengetahui tingkat pengetahuan ibu. Hasil menunjukkan 32,26% balita berstatus imunisasi dasar tidak lengkap, selain itu masih terdapat 6,45% berstatus gizi kurang dan 9,68% gizi lebih, namun setelah pemberian edukasi tingkat pengetahuan ibu berada dalam kategori baik. Orang tua berdaya dan sadar akan kebutuhan kesehatan anak, maka akan tercipta generasi yang berkualitas.